Persistent organic pollutants in the Antarctic coastal environment and their bioaccumulation in penguins. (September 2016) - Mwangi, John Kennedy; Lee, Wen-Jhy; Wang, Lin-Chi; Sung, Ping-Jyun; Fang, Lee-Shing; Lee, Yen-Yi; Chang-Chien, Guo-Ping
Abstract: Persistent organic pollutants (POPs), including polychlorinated dibenzo-p-dioxins and dibenzofurans (PCDD/Fs), polychlorinated biphenyls (PCBs), polybrominated dibenzo-p-dioxins and dibenzofurans (PBDD/Fs), polybrominated biphenyls (PBBs), and polybrominated diphenyl ethers (PBDEs), have been identified in penguins, lichens, soils, and ornithogenic soils in the Antarctic coastal environment in this study. To the best of our knowledge, no previous study has reported PBDD/F and PBB data from Antarctica. The POP mass contents in penguins were in the following order: PCBs >> PBDEs >> PCDD/Fs; PCBs were the dominant pollutants (6310–144, 000 pg/g-lipid), with World Health Organization toxic equivalency values being 2–14 times higher than those of PCDD/Fs. Long-range atmospheric transport is the most primary route by which POPs travel to Antarctica; however, local sources, such as research activities and penguin colonies, also influence POP distribution in the local Antarctic environment. In penguins, the biomagnification factor (BMF) of PCBs was 61.3–3760, considerably higher than that for other POPs. According to BMF data in Adélie penguins, hydrophobic PBDE congeners were more biomagnified at log Kow  > 6, and levels decreased at log Kow  > 7.5 because larger molecular sizes inhibited transfer across cell membranes. Highlights: PCBs are the dominant class of POPs in penguins. Local sources influence environmental POP contents. Combustion sources at research bases increase PBDD/F and PBDE contents in lichens. Penguins contribute PCBs and PBDEs to the soil through fecal matter. PBDE BMFs in Adélie penguins decreased at log Kow  > 7.5. Abstract : Compared with other POPs, PCBs are the dominant pollutant in penguins, with WHO-TEQ values 2–14 times higher than those of PCDD/Fs.